IMPROVING SOCIAL SKILL AND CIVICS LEARNING OUTCOME THROUGH PROBLEM-BASED LEARNING (PBL) ASSISSTED WITH DIGITAL LITERACY TO THE XI GRADERS OF TITL VOCATIONAL HIGH SCHOOL SMK GAMALIEL 1 MADIUN - Basuki Basuki; Sudarmiani Sudarmiani; Moh. Rifa’i (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
The current study, which is a classroom action research, aims to improve: (1) the learning process; and (2) the social skill and civics learning outcome of the XI graders of TITL vocational high school of SMK Gamaliel 1 Madiun through implementing PBL assisted by digital literacy. This involved 35 students and lasted from August 2019 to February 2020. Data were gathered through (1) interview, (2) observation, (3) document, (4) assignments/tests. On the basis of the 4 cycles, it was found that the average score of the social skill of: cycle 1 was 61.23; cycle 2 was 72.03; cycle 3 was 82.09. There was improvement as much as 10.80 from cycle 1 to cycle 2, and 10.06 from cycle 2 to cycle 3. Regarding learning outcome, the average scores were: cycle 1 = 65.00; cycle 2 = 71.14, and cycle 3 = 76.71. There were, therefore, improvement as much as 6.15 from cycle 1 to cycle 2 and 5.57 from cycle 2 to cycle 3. To put in brief, implementing PBL assisted by digital literacy to the XI graders of TITL vocational high school of SMK Gamaliel 1 Madiun improved their: (1) social skill, and (2) civics learning outcome.